Diagnosis and Management of Deltoid Ligament Insufficiency. Issue 3 (19th August 2019) - Sridharan, Sarup S.; Dodd, Andrew
Background: Surgical management of patients with acute and chronic ankle instability (CAI) has historically focused on the lateral ligament complex. Recent studies in CAI patients have shown that magnetic resonance imaging (MRI) and arthroscopy demonstrate concomitant injury to the deltoid ligament complex We performed a systematic review to determine if consistent clinical, diagnostic imaging, or arthroscopic findings of deltoid ligament injury in the setting of CAI have been described. In addition, we sought to determine if treatment options and/or clinical outcomes have been described. Methods: A systematic review was conducted using the PubMed, MEDLINE, and Embase databases. Articles were included if they had a majority of patients 18 years of age or older, focused on deltoid ligament injury in ankle instability, and reported diagnostic and/or treatment methods. Articles were excluded if the study focused on the deltoid ligament in the acute fracture setting. All included articles were assessed for diagnostic criteria, treatments, and patient outcomes. Results: Our search yielded 157 articles, of which a total of 13 were included in our study. Arthroscopy was described as the gold standard to diagnose and evaluate the severity of deltoid ligament injury, however, little objective data on the arthroscopic diagnosis of deltoid ligament insufficiency was reported. MRI was the imaging modality of choice to evaluate deltoid ligament injury and had a high sensitivity and specificity when compared with arthroscopy. No standard MRI diagnostic criteria for deltoid ligament injury were identified in the literature. Specific treatment techniques and long-term outcomes were not well described in the manuscripts included in this review. Conclusion: There is limited knowledge on deltoid ligament insufficiency in the setting of chronic ankle instability. Criteria for characterizing deltoid ligament damage with diagnostic imaging appear to be evolving, but there is no standard classification. Only 1 author has described a method to evaluate deltoid ligament competency on arthroscopic examination. There are currently no objective data to guide treatment decisions. Level of Evidence: Level III.